Eugene Onegin the Cold War Monument: How Edmund Wilson Quarreled with Vladimir Nabokov - Tim Conley (Studies in 20th & 21st Century Literature, 2014)
The tale of how Edmund Wilson quarreled with Vladimir Nabokov over the latter’s 1964 translation of Eugene Onegin can be instructively read as a politically charged event, specifically a “high culture” allegory of the Cold War. Dissemination of anti-Communist ideals (often in liberal and literary guises) was the mandate of the Congress for Cultural Freedom, whose funding and editorial initiatives included the publication of both pre-Revolution Russian literature and, more notoriously, the journal Encounter (1953-1990), where Nabokov’s fiery “Reply” to Wilson appeared. This essay outlines the propaganda value of the Onegin debate within and to Cold War mythology.
Keywords: Nabokov; Wilson; translation; Pushkin; Onegin; Cold War